An investigation into the fatigue and corrosion fatigue properties of two high strength low alloy steels and their HAZ’s. - Drury, J. A. (Cranfield University, 1992)
Testing was performed on three point bend specimens machined from parent plate and welded samples machined such that the crack propagated down the heat affected zone. Specimens were subjected to tension-tension loading using a stress ratio of 0.6 and a testing frequency of 0.5 Hz. Tests were performed in air and in a synthetic sea water solution. Three levels of corrosion protection were investigated, freely corroding, protected at -800 mV and over protected at -1100 mV. The resulting crack growth rate data were plotted on a log scale against the log of the stress intensity range. This made comparisons between different conditions and materials easier. Both high strength steels and the heat affected zones associated with their weldments compared favourably with BS4360:50D structural steel when tested in air and with a cathodic potential of -800 mV. Using over protection conditions the materials showed a susceptibility to hydrogen concentration. A particularly sensitive technique was used to investigate the effects of heat affected zone microstructures on the crack propagation rate. This was achieved using a continuous monitoring gauge mounted onto the side of the specimen. The gauge was used to obtain the crack length and a computer was coupled to the fatigue machine to control the applied loads. The resulting data showed that there was a variation in growth rates between different weldment regions which was in turn influenced by the weld heat input used. The other finding was that when low heat inputs were used for welding there was rapid increase in crack growth rate associated with the coarse grained region, which was attributed to the aligned carbides of this region which act to stop crack blunting. This effect was only seen in the 1.5 kJ/mm weld, higher heat inputs cause a break up of these carbides and hence the crack is able to blunt.